Equipping South African Foundation Phase Pre-Service Teachers with Computational Thinking through Unplugged Coding - Tanja Coetzer; Zelda De Beer (Indonesian Journal of Early Childhood Education Studies, 2025)
The integration of computational thinking (CT) in South Africa’s Foundation Phase curriculum is gaining momentum, particularly with the introduction of coding and robotics. However, full-scale implementation has been delayed by limited infrastructure, insufficient teacher training, and unequal access to resources. This article reports qualitative findings from the 2024 pilot phase of the Foundation Phase Unplugged Coding Project conducted at the Cape Peninsula University of Technology (CPUT). Guided by a Scholarship of Teaching and Learning (SoTL) approach, the study explores non-digital methods for developing CT and examines short-term shifts in pre-service teachers’ knowledge, strategies, and confidence. Unplugged coding provides equitable, hands-on, and collaborative problem-solving experiences that are independent of digital devices, making them relevant to both well-resourced and under-resourced schools. Using service learning as a training model, the project aligns with national policy and investigates pre-service teachers’ engagement in coursework, classroom implementation, and reflective practice. Reflective essays reveal how pre-service teacher participants implemented, understood, and adapted CT pedagogy across diverse South African classrooms, developing competence, problem-solving strategies, and CT literacy during teaching practicum. The study contributes empirical evidence to the emerging field of CT in early education and demonstrates the value of a SoTL approach for strengthening teacher education research.